(untitled) (The Review of Diabetic Studies, 2025)
Type 2 diabetes mellitus (T2DM) is a long-standing metabolic disorder marked by persistent elevation of blood glucose levels due to insulin resistance and defective insulin secretion. Over the years, oxidative stress has been identified as one of the major factors contributing to the development and progression of diabetic complications. Visfatin, an adipokine mainly secreted by visceral adipose tissue, is believed to play an important role in inflammatory and metabolic processes associated with diabetes mellitus. In view of these observations, the present study was undertaken to assess the relationship between plasma visfatin levels of oxidative stress markers in patients with T2DM. A study of 300 participants150 individuals diagnosed with type 2 diabetes and 150 healthy controls, who were matched for age and sex taken for a case-control study. Plasma visfatin, fasting blood glucose (FBG), glycated haemoglobin (HbA1c), malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) were measured using fasting venous blood samples. The enzyme-linked immunosorbent assay (ELISA) was used to assess the levels of plasma visfatin. Standard biochemical techniques were used to assess oxidative stress indicators. SPSS version 25.0 was used for statistical analysis. Plasma visfatin levels were significantly elevated in T2DM patients compared to controls (p < 0.001). Oxidative stress marker MDA showed a significant increase, whereas antioxidant enzymes SOD, CAT, and GPx were significantly decreased in diabetic patients. Plasma visfatin demonstrated a positive correlation with FBG, HbA1c, and MDA, while showing a negative correlation with antioxidant enzyme levels. The findings suggest that elevated plasma visfatin is associated with increased oxidative stress in T2DM patients. Visfatin may serve as a potential biomarker for oxidative stress and metabolic dysregulation in diabetes mellitus.